Agroindústria canavieira e formação territorial paulista: do engenho escravista à usina de açúcar e álcool (1530-1930) - Rodolfo A. M. Pelegrin (Confins)
This article discusses the development of the sugar cane agroindustry and its relations with the territorial formation of São Paulo state, from the installation of the Portuguese colonial company to the constitution of the mill model that characterizes the sector in the 20th century. Using bibliographic, image and data research, image production and edition, the article illustrates the productive and spatial movements that characterize those relationships, highlighting geopolitical, economic, institutional, territorial and technical aspects. The exhibition is organized with a proposal of periodization, which crosses a slave and an industrial period, during which sugar production evolves productively and spatially, and conforms to the integrated agro-industrial and landowning model of the present. We then seek to distinguish transformations and permanencies, and to characterize the links between the commercial sugarcane expansion and the constitution of the São Paulo territory, in their contexts and determinations, with the elaboration of a synthesis table.